Plant Performance Indicator - Nor Azyyati Binti Azmi, Nor Azyyati (Universiti Teknologi Petronas, 2009)
This report basically discusses the literature research done and basic understanding of the chosen topic which is ‘Plant Performance Indicator’. Plant Performance Indicator is a quantifiable measurement that reflects the critical success factors of an organization. It helps an organization to define and measure progress toward organizational goals. Normally, evaluation of the overall plant performance takes time and involved a lot of steps. This happens when each performance is evaluated individually and usually the plant performance indicator is used for long term consideration (within a year). Therefore, the study is aimed to identify several indicators used in evaluating plant performance and to select several best indicators in order to develop equipment monitoring tool using spreadsheet for process monitoring. The objective of developing the tool is to monitor and evaluate the performance of the plant within both short and long term consideration. The indicator can be applied at anytime and this will surely provide enough time to the organization to take immediate mitigation action if something goes wrong with their plant performance. Then, this tool will be implemented to a case study (small-scaled plant) in order to compare the result assess by the tool with the tools that is already used by the company. The framework of the project starts with the identification and selection of several plant performance indicators and followed by the process of developing the tool. The tool will be equipped with three main indicators namely environmental performance indicator, safety performance indicator and productivity performance indicator. This Final Year Project (FYP) is carried out under the supervision of Associate Professor Dr. Azmi bin Mohd Shariff